Clinically Adult Onset of a Leptomeningeal Cyst After Head Trauma in Childhood: Case Report and Review of the Literature. Issue 3 (August 2016) - Kale, Aydemir; Aydoğmuş, Evren; Açikgöz, Bektaş
Abstract : Traumatic leptomeningeal cysts, also known as growing skull fractures, are a rare but serious complication of childhood cranial fractures and a very rare complication following head traumas in adults. We present the case of a 35-year-old woman with drug-resistant epileptic seizures caused by a traumatic leptomeningeal cyst from the head injury she suffered at the age of 18 months. Surgical treatment was performed with the removal of the leptomeningeal cyst, dural repair, and cranioplasty. She had no more epileptic seizures at her follow-ups. Although it is rare, after head trauma in childhood, adult patients have often complained of epileptic seizure. Surgical treatment is necessary to control the illness.